ARIOT: Permainan Edukasi Pertanian Cerdas Sebagai Upaya Menumbuhkan Agro-Entrepreneurship Pada Siswa Penyandang Disabilitas Tuna Rungu - Kurniasari, Arvita Agus; Puspitasari, Trismayanti Dwi; Kurniasari, Leli (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Sekolah Luar Biasa (SLB) are education for students who have difficulty in participating in the learning process because they have special physical, emotional, mental and social needs, but have the potential for intelligence and special talents. SLB Negeri Jember also faces problems in the educational process, one of which is deaf students who experience barriers and disturbances in verbal communication both expressively and receptively. This resulted in the message being conveyed and received a lot of misunderstanding of meaning. Online learning activities during the Covid-19 pandemic at SLB cannot be fully carried out online due to the limitations of students. The activity plans and solutions provided for the service are using the Android-based Augmented Reality (AR) game learning method. Making this method begins with the design sprint stage to communicate with the relevant team, namely psychologists and teachers, followed by AR programming and ends with validation so that the application has been tested for students with special needs. The results of the implementation to determine the level of acceptance of the use of the application is obtained a percentage value of 80%. Suggestions for the next development are the implementation of direct tools for IoT so that students gain new knowledge about sensor implementation